Method for preparing high-purity and high-crystallinity CaLa2S4 infrared ceramic powder

CALA2S4 powder front drives are synthesized through liquid reflection and uses sulfidamide as a catalyst and sealing agent. Combined with the low temperature sulfurization method, the problem of the purity, sintering and crystallization of CALA2S4 infrared ceramic powder in the existing technology solves the problem , Achieve high -purity, high -crystalline and high -fever CALA2S4 powder preparation.

CN119330715AActive Publication Date: 2025-01-21XUZHOU NORMAL UNIVERSITY

Patent Information

Application Number
CN202411429966.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-21
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

In the preparation of CaLa2S4 infrared ceramic powder, the existing technology has problems of low purity, low sintering properties, large particle size and poor crystallinity. At the same time, the vulcanization process is complex and the risk is high, and the sintering time is long, resulting in powder particles. Overgrowth.

Method used

The CaLa2S4 powder precursor is synthesized using a liquid phase reaction. Thioacetamide is used as a catalyst and end-capping agent. The impurity elements in the precursor are removed through a thermal decomposition reaction, and then vulcanized at low temperature to ensure the stoichiometric ratio of sulfur. Avoid carbon pollution.

Benefits of technology

The purity, crystallization, and sinterability of the CALA2S4 powder have been improved, the particle size is reduced, the process of the process is simplified, the cost of raw materials is reduced, and the sulfur treatment is performed within a specific temperature range, avoiding the problem of missing sulfur missing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330715A_ABST
    Figure CN119330715A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing CaLa2S4 infrared ceramic powder with higher purity and better crystallinity, which comprises the following steps: synthesizing a precursor in a wet chemical path, carrying out thermal decomposition reaction under a relatively low-temperature condition, and carrying out low-temperature vulcanization to form a CaLa2S4 phase, thereby preparing the CaLa2S4 infrared ceramic powder with higher purity and better crystallinity. According to the method, a CaLa2S4 precursor is chemically synthesized through a liquid phase reaction, thioacetamide serves as a catalyst and an end-capping reagent, impurity elements in the precursor are removed through a thermal decomposition reaction, then the stoichiometric ratio of sulfur is recovered through a low-temperature vulcanization method, and the submicron CaLa2S4 powder is obtained through vulcanization. The method is simple in preparation process, high in synthesis efficiency and low in raw material cost, and the prepared CaLa2S4 powder has the advantages of being high in purity, good in crystallinity and sinterability, small in particle size and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of new material technology, and specifically relates to a method for preparing high-purity and high-crystallinity CaLa 2 S 4 Infrared ceramic powder method. Background Art

[0002] In the early 1980s, Cala 2 S 4 Solid solution compounds appear as alternative window materials to ZnS. CaLa 2 S 4 It is through Ca 2+ Doping attempts to improve γ-La 2 S 3 Infrared performance prepared, CaLa 2 S 4 The compound has a thorium phosphide-type cubic structure (Th 3 P 4 ), high melting point (Tm = 2300K), large bandgap (E = 2.7eV), wide optical transmission band (0.4-18μm), due to the characteristics of Th 3 P 4 Type structural defects, Ca 2+ It can fill the lattice vacancies, making the lattice change smaller, adding a large amount of Ca 2+ Helps to obtain a stable cubic phase at low temperatures. CaLa 2 S 4 Transparent ceramics have the advantages of excellent infrared transmittance, high melting point and high hardness, and have good resistance to wind, sand and rain erosion. They are ideal candidate materials for future infrared window materials.

[0003] CaLa 2 S 4 The research mainly focuses on CaLa 2 S 4 In terms of powder preparation, CaLa with high purity, good crystallinity and high sintering activity 2 S 4 Ceramic powder is the key to successfully preparing high-quality CaLa 2 S 4 One of the key factors of infrared transparent ceramics. 2 S 4 The powder method mostly adopts a two-step method: the first step is to synthesize CaLa, a mixture of calcium and lanthanum ions. 2 S 4 precursors, which are then subsequently reacted in H 2 S or CS 2 Sulfurized in the atmosphere and converted into CaLa2 S 4 powder.

[0004] At present, the synthesis of CaLa 2 S 4 The specific method of powder is as follows: (1) Lanthanum nitrate, calcium nitrate and thioacetamide are used as starting materials to prepare a nitrate solution and then heated to produce a precursor, and then the precursor is heated in H 2 (2) preparing a nitrate solution with calcium nitrate and lanthanum nitrate solution as raw materials, then spraying the nitrate solution into a hot furnace at 800°C to produce a precursor, and then heating the precursor in H 2 SH 2 (3) La metal powder and dry methanol are added to a pressureless container, with a small amount of mercuric chloride and mercuric iodide as catalysts, and kept warm for 30 days. Subsequently, Ca metal powder is added to the container to form methanol salt; methanol salt is decomposed in vacuum and heated in H 2 (4) adding lanthanum nitrate and calcium nitrate to distilled water to prepare a stock solution; then stirring ammonium carbonate and ammonium hydroxide solutions and quickly dispersing the stock solution in the solution; ultrasonically dispersing and filtering the precipitate, spray freezing the precipitate, and then drying it for several days; the dried precursor is sintered at high temperature in an oxygen atmosphere, and then heated to room temperature in H 2 S sulfide; (5) lanthanum acetate (La(CH 3 COO 3 ) and calcium acetate (Ca(CH 3 COO 2 ) was dissolved in deionized distilled water, sprayed into a large liquid nitrogen dehydration bottle and freeze-dried for several days, then the precursor was calcined in a pure oxygen atmosphere, and finally heated in H 2 S atmosphere to form sulfide; (6) calcium carbonate (CaCO 3 ) and lanthanum carbonate (La 2 (CO 3 ) 3 ) powders were mixed in the correct stoichiometric ratio, placed in a graphite boat and placed in a silica-glass furnace tube for several days, and then heated in H 2 (7) co-precipitating calcium oxalate and lanthanum oxalate from a nitrate solution, filtering and drying the resulting precipitate, and then heating the precursor in air to convert it into an oxide, and finally heating the precursor in H 2 The mixed oxide product is converted into sulfide by heating in an S atmosphere.

[0005] However, the CaLa prepared by the above preparation method 2 S 4The powder has the disadvantages of low purity, low sinterability, large particle size (μm level) and poor crystallinity. At the same time, the sulfurization process is complicated and dangerous, and the long sintering time leads to excessive growth of powder particles. 2 S 4 At high sintering temperatures (ie, T ≥ 1000°C), reduction will occur and phase change will occur, causing the sample to turn black and affecting the transmittance of the final ceramic sample. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing high-purity and high-crystalline CaLa 2 S 4 The method for preparing infrared ceramic powder has a simple preparation process and can improve the prepared CaLa 2 S 4 The purity, crystallinity and sinterability of the powder reduce the 2 S 4 Particle size of powder.

[0007] To achieve the above object, the present invention provides a method for preparing high-purity and high-crystalline CaLa 2 S 4 The method of producing infrared ceramic powder comprises the following steps:

[0008] S1. Dissolve sodium diethyldithiocarbamate trihydrate powder and phenanthroline monohydrate powder in anhydrous ethanol respectively, then mix the sodium diethyldithiocarbamate alcohol solution and the phenanthroline alcohol solution and stir vigorously to obtain solution A;

[0009] S2, dissolving lanthanum chloride heptahydrate powder and calcium chloride dihydrate powder in anhydrous ethanol respectively, then mixing the lanthanum chloride alcohol solution and the calcium chloride alcohol solution and stirring them uniformly to obtain solution B, then adding solution B dropwise to solution A prepared in step S1, and stirring vigorously to obtain a yellow solution;

[0010] S3, dissolving thioacetamide powder in anhydrous ethanol to prepare a reagent that serves as both a catalyst and a capping agent, then dropping the catalyst and the capping agent into the yellow solution prepared in step S2, heating the reaction, centrifuging and washing the yellow solution with anhydrous ethanol for multiple times to obtain a yellow precipitate;

[0011] S4, placing the yellow precipitate obtained in step S3 in an oven to dry to obtain a yellow powder, and then heat-treating the yellow powder in air to remove impurities to generate a gray powder;

[0012] S5, placing the gray powder obtained in step S4 in a tube furnace, one end of which is connected to a mixture of argon and hydrogen, and when the temperature is raised to a specific sulfurization temperature, the mixture of argon and hydrogen passes through the CS 2Liquid, after a period of sulfurization reaction, the temperature is lowered to end the sulfurization process, and finally high-purity and good-crystallization CaLa 2 S 4 Infrared ceramic powder.

[0013] Preferably, in step S1, the concentrations of the sodium diethyldithiocarbamate alcohol solution and the phenanthroline alcohol solution are both 0.2 mol / L; in solution A, the molar ratio of sodium diethyldithiocarbamate trihydrate powder to phenanthroline monohydrate powder is 1:1.

[0014] Preferably, in step S2, the concentration of the lanthanum chloride alcohol solution is 0.05 mol / L, and the concentration of the calcium chloride alcohol solution is 0.02 mol / L; in solution B, the molar ratio between the lanthanum chloride heptahydrate and the calcium chloride dihydrate is (2-2.5):1.

[0015] Preferably, in step S3, the heating reaction temperature is 60-80° C. and the reaction time is 1-2 h.

[0016] Preferably, in step S3, the concentration of thioacetamide powder in the catalyst and the capping agent is 0.1 mol / L.

[0017] Preferably, in step S3, centrifugal washing is performed at least 4 times.

[0018] Preferably, in step S4, the heat treatment temperature is 450-650° C., and the heat treatment time is 3-6 hours.

[0019] Preferably, in step S4, the drying temperature is 50-70° C. and the drying time is 24-36 hours.

[0020] Preferably, in step S5, in the argon-hydrogen mixed gas, the volume ratio of argon to hydrogen is 95:5; and the gas flow rate is 25-75 ml / min.

[0021] Preferably, in step S5, the specific vulcanization temperature is 600-1000°C, the vulcanization reaction temperature is 600-1000°C, and the vulcanization reaction time is 3-6h.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention first uses liquid phase reaction to synthesize CaLa 2 S 4 The powder precursor is prepared by using thioacetamide as a catalyst and end-capping agent, and then the impurity elements in the precursor are removed by thermal decomposition reaction. Then, the stoichiometric ratio of sulfur is restored by low-temperature vulcanization method, and micron-sized CaLa is obtained by vulcanization. 2 S 4The present invention only performs sulfurization treatment within a specific temperature range, which ensures the stoichiometric ratio of sulfur while avoiding carbon pollution, effectively solving the problem of CaLa 2 S 4 The problem of sulfur deficiency in the preparation of infrared ceramic powders; this method has simple preparation process, high synthesis efficiency and low raw material cost, and the prepared CaLa 2 S 4 The powder has the advantages of high purity, good crystallinity, good sintering properties and small particle size. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The CaLa prepared in step S4 of the present embodiment 2 S 4 X-ray diffraction pattern of powder precursor;

[0025] Figure 2 The CaLa prepared in step S4 of the present embodiment 2 S 4 TG-DSC spectrum of powder precursor;

[0026] Figure 3 The CaLa prepared in step S4 of the present embodiment 2 S 4 SEM image of powder precursor;

[0027] Figure 4 The CaLa prepared in step S4 of the present embodiment 2 S 4 Fourier infrared spectrum of powder precursor;

[0028] Figure 5 The CaLa prepared in step S4 of the present embodiment 2 S 4 X-ray diffraction pattern of powder precursor after thermal decomposition;

[0029] Figure 6 The CaLa prepared in the embodiment of the present invention 2 S 4 X-ray diffraction pattern of powder;

[0030] Figure 7 The CaLa prepared in the embodiment of the present invention 2 S 4 SEM and elemental EDS spectra of powder;

[0031] Figure 8 The CaLa prepared in step S4 of the present embodiment 2 S 4 Physical picture of powder precursor;

[0032] Fig. 9 The CaLa prepared in the embodiment of the present invention 2 S 4 Physical picture of the powder. DETAILED DESCRIPTION

[0033] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0034] The raw materials and reagents used in the following examples, unless otherwise specified, are from conventional commercial stores.

[0035] Na(Ddtc)·3H 2 O powder, phen·H 2 O powder, LaCl 3 7H 2 O powder, CaCl 2 ·2H 2 O powder and TAA powder are analytical grade powders, CS 2 The reagents were of analytical grade.

[0036] Example

[0037] A method for preparing high-purity and high-crystalline CaLa 2 S 4 The method of producing infrared ceramic powder comprises the following steps:

[0038] S1, 20mmol sodium diethyldithiocarbamate trihydrate powder (Na(Ddtc)·3H 2 O) and 20 mmol phenanthroline monohydrate powder (phen·H 2 O) were dissolved in 100 ml of anhydrous ethanol, then the Na(Ddtc) alcohol solution and the phen alcohol solution were mixed and stirred vigorously at 300 r / min to obtain solution A;

[0039] S2, 5mmol lanthanum chloride heptahydrate powder (LaCl 3 7H 2 O) and 2.174 mmol calcium chloride dihydrate powder (CaCl 2 ·2H 2 O) are respectively dissolved in 100 ml of anhydrous ethanol, and then the lanthanum chloride alcohol solution and the calcium chloride alcohol solution are mixed and stirred at a speed of 300 r / min to obtain a solution B, and then the solution B is added dropwise to the solution A prepared in step S1, and vigorously stirred at a speed of 400 r / min to obtain a yellow solution;

[0040] S3, dissolving 10 mmol of thioacetamide (TAA) powder in 100 ml of anhydrous ethanol to prepare a catalyst and a capping agent, then adding the catalyst and the capping agent dropwise to the yellow solution prepared in step S2, heating to 70° C. to react for 2 h, centrifuging and washing the yellow solution 4 times with anhydrous ethanol to obtain a yellow precipitate;

[0041] S4. The yellow precipitate obtained in step S3 is placed in a 70°C oven and dried for 24 hours to obtain a yellow powder, which is CaLa. 2 S 4 Powder precursor, the actual picture is as follows Figure 8 As shown; the yellow powder is then heat-treated in air to remove impurities to generate gray powder, the heat treatment temperature is 500°C, and the heat treatment time is 5h;

[0042] S5. Place the gray powder obtained in step S4 in a tube furnace. One end of the tube furnace is connected to a mixture of argon and hydrogen (the volume ratio of argon to hydrogen is 95:5) with a gas flow rate of 30 ml / min. When the temperature rises to the specific sulfurization temperature of 700°C, the mixture of argon and hydrogen passes through the CS 2 The liquid begins to vulcanize, and after being kept at 1000℃ for 3 hours, the vulcanization process ends when the temperature drops to 700℃, and finally high-purity and high-crystalline CaLa is prepared. 2 S 4 Infrared ceramic powder, its X-ray diffraction spectrum, SEM and element EDS spectrum, and physical picture are as follows Figure 6 , Figure 7 and Fig. 9 shown.

[0043] The CaLa obtained in step S4 2 S 4 The powder precursor was subjected to X-ray diffraction analysis, TG / DSC test, electron microscope scanning, and infrared spectrum analysis in turn, and the results were as follows: Figure 1-Figure 4 The gray powder obtained in step S4 was subjected to X-ray diffraction analysis, and the results were as follows Figure 5 shown.

[0044] from Figure 1 It can be seen that the precursor is an oxide with poor crystallinity, and needs to be post-treated to form a sulfide with high crystallinity. Figure 2 It can be seen that the precursor undergoes two weight loss processes to remove impurities within the range of 1200℃, and the precursor thermal decomposition temperature and sulfurization post-treatment temperature are set according to the two weight loss temperatures; Figure 3 It can be seen that the precursor is a nano-scale powder; Figure 4 It can be seen that there are many organic elements in the precursor that need to be purified; Figure 5It can be seen that sulfur oxides appear in the powder after thermal decomposition and the crystallinity is better than that of the precursor, but it still needs to be further purified and the crystallinity improved.

[0045] from Figure 6 It can be seen that the powder phase after sulfurization treatment is the desired phase with high purity and good crystallinity; Figure 7 As can be seen in the graphene, the post-cured powder consists of submicron sized particles and the presence of expected cations and anions can be seen.

Claims

1. A method for preparing high-purity, high-crystallinity CaLa2S4 infrared ceramic powder, characterized in that: The following steps are involved: S1. Dissolve sodium diethyldithiocarbamate trihydrate powder and phenanthroline monohydrate powder in anhydrous ethanol respectively, then mix the sodium diethyldithiocarbamate alcohol solution and the phenanthroline alcohol solution and stir vigorously to obtain solution A; S2, dissolving lanthanum chloride heptahydrate powder and calcium chloride dihydrate powder in anhydrous ethanol respectively, then mixing the lanthanum chloride alcohol solution and the calcium chloride alcohol solution and stirring them uniformly to obtain solution B, then adding solution B dropwise to solution A prepared in step S1, and stirring vigorously to obtain a yellow solution; S3, dissolving thioacetamide powder in anhydrous ethanol to prepare a reagent that serves as both a catalyst and a capping agent, then dropping the catalyst and the capping agent into the yellow solution prepared in step S2, heating the reaction, centrifuging and washing the yellow solution with anhydrous ethanol for multiple times to obtain a yellow precipitate; S4, placing the yellow precipitate obtained in step S3 in an oven to dry to obtain a yellow powder, and then heat-treating the yellow powder in air to remove impurities to generate a gray powder; S5. The gray powder obtained in step S4 is placed in a tubular furnace. One end of the tubular furnace is connected to a hydrogen-argon mixed gas. When the temperature is raised to a specific sulfurization temperature, the hydrogen-argon mixed gas is passed through the CS2 liquid. After a period of sulfurization reaction, the temperature is lowered to end the sulfurization process, and finally a CaLa2S4 infrared ceramic powder with high purity and good crystallinity is prepared.

2. The method for preparing high-purity, high-crystallinity CaLa2S4 infrared ceramic powder according to claim 1, characterized in that: In step S1, the concentrations of the sodium diethyldithiocarbamate alcohol solution and the phenanthroline alcohol solution are both 0.2 mol / L; in solution A, the molar ratio of the sodium diethyldithiocarbamate trihydrate powder to the phenanthroline monohydrate powder is 1:

1.

3. A method for preparing high-purity, high-crystallinity CaLa2S4 infrared ceramic powder according to claim 1 or 2, characterized in that: In step S2, the concentration of the lanthanum chloride alcohol solution is 0.05 mol / L, and the concentration of the calcium chloride alcohol solution is 0.02 mol / L; in solution B, the molar ratio between the lanthanum chloride heptahydrate and the calcium chloride dihydrate is (2-2.5):

1.

4. A method for preparing high-purity, high-crystallinity CaLa2S4 infrared ceramic powder according to claim 1 or 2, characterized in that: In step S3, the heating reaction temperature is 60-80°C and the reaction time is 1-2h.

5. A method for preparing high-purity, high-crystallinity CaLa2S4 infrared ceramic powder according to claim 1 or 2, characterized in that: In step S3, the concentration of thioacetamide powder in the catalyst and the end-capping agent is 0.1 mol / L.

6. A method for preparing high-purity, high-crystallinity CaLa2S4 infrared ceramic powder according to claim 1 or 2, characterized in that: In step S3, centrifugation washing is performed at least 4 times.

7. A method for preparing high-purity, high-crystallinity CaLa2S4 infrared ceramic powder according to claim 1 or 2, characterized in that: In step S4, the heat treatment temperature is 450-650° C., and the heat treatment time is 3-6 hours.

8. A method for preparing high-purity, high-crystallinity CaLa2S4 infrared ceramic powder according to claim 1 or 2, characterized in that: In step S4, the drying temperature is 50-70°C and the drying time is 24-36h.

9. A method for preparing high-purity, high-crystallinity CaLa2S4 infrared ceramic powder according to claim 1 or 2, characterized in that: In step S5, in the argon-hydrogen mixed gas, the volume ratio of argon to hydrogen is 95:5; and the gas flow rate is 25-75 ml / min.

10. A method for preparing high-purity, high-crystallinity CaLa2S4 infrared ceramic powder according to claim 1 or 2, characterized in that: In step S5, the specific vulcanization temperature is 600-1000°C, the vulcanization reaction temperature is 600-1000°C, and the vulcanization reaction time is 3-6h.

Citation Information

Patent Citations

  • Method of manufacturing a sulfide-based ceramic element, particularly for ir-optics applications

    CN107001153A

  • Anion step-by-step substituted spinel electrode material for zinc ion battery and preparation method thereof

    CN118335916A

  • Terminal device, central device, train information management system, and train information management method

    US20190202485A1

Cited By

  • Method for preparing high-purity calcium-lanthanum-sulfur transparent ceramic powder by adopting gas-solid method and application of obtained product

    CN121651414A

  • Method for preparing high-purity calcium lanthanum sulfide transparent ceramic powder by gas-solid method and application of the product obtained

    CN121651414B